Towards Precision Rheumatology? - Roberto Paganelli; Eleonora Celletti (Journal of Arthritis Research and Therapy, 2018)
The possibility of tailoring treatment on specific characteristics of patients – i.e. personalized medicine – has received attention in the field of rheumatic diseases since biological DMARDs targeting a unique pathway have become available. However the idea of personalized rheumatology has advanced slowly, at different paces in different disease groups, and it is only now surfacing in the recommendations for assessment and treatment of rheumatoid arthritis (RA). Many of the difficulties encountered stem from the recognition that many rheumatic diseases are not a single entity but encompass different subsets identified on the basis of genetic traits, cellular and molecular characterization both in blood and in tissues, laboratory markers and clinical manifestations (most notably in SLE). These differences suggest a multiplicity of pathogenetic triggers, whose various combination results in slightly or very diverse presentations. Developments in companion diagnostics and the identification of distinct subsets within complex syndromes are going to allow the definition of predictive biomarkers able to reduce poor treatment outcome, thus ensuring that we are treating “the right patient with the right drug”.
Keywords: Rheumatic Diseases